Effect of ventilation control settings on ammonia and odour emissions from a pig rearing building. (April 2020) - Tabase, Raphael K.; Millet, Sam; Brusselman, Eva; Ampe, Bart; De Cuyper, Carolien; Sonck, Bart; Demeyer, Peter
Abstract : The objective is to investigate whether NH3 and odour emissions can be lowered by implementing three different ventilation control settings (VCS) as low-cost mitigation techniques. In treatment 1 (T1) the set-point temperature ( Tset ) was set +2 °C higher than the reference strategy (CON). In treatment 2 (T2), the minimum ( V min ) and maximum ( V max ) ventilation settings were set to 75% and 90% of the CON, respectively. For treatment 3 (T3), the Tset was +1 °C higher than the CON, while the V min and V max settings were initially set at 25% and 80% of the CON but gradually increased during the fattening period. The results implied that T1 was the best VCS, as it significantly lowered odour emissions compared to the CON by 34%. Despite the significant decrease in ventilation rate, the overall hourly average NH3 emissions did not differ between treatments T1, T2, T3 and CON. However, based on the VERA protocol (https://www.vera-verification.eu/test-protocols/ ), annual NH3 emission factors were calculated and demonstrated the potential of T1 to decrease NH3 emissions by 11% compared to the CON. The lack of significant differences in the overall hourly average NH3 emissions between T1, T2, T3 and the CON was in part due to the seasonal variations in pig housing airflow patterns affecting the air exchange rate in the slurry pit. This indicates that, despite the importance of the ventilation rate on emissions, the effect of the indoor airflow pattern on the gaseous release from the slurry pit into the building is crucial. Highlights: Impact of ventilation settings on NH3 and odour emissions tested. Research performed in a fully-slatted pig house with underfloor air inlets. Increasing set-point temperature by +2 °C reduced odour emission by 34% but not NH3 . Seasonal changes in slurry pit air exchange rate affected NH3 emission reduction. No significant differences in pig performance found between ventilation settings.